2018
DOI: 10.3390/polym10050552
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Poly(Propylene Carbonate) with Thermoplastic Networks: A One-Pot Synthesis from Carbon Dioxide, Propylene Oxide, and a Carboxylic Dianhydride

Abstract: Thermally and mechanically enhanced poly(propylene carbonate) (PPC) with networks was prepared by adding a cyclic carboxylic dianhydride, bicyclo(2,2,2)oct-7-ene-2,3,5,6-tetracarboxylic dianhydride (BTCDA), in the CO2/propylene oxide (PO) copolymerization. The obtained copolymers were characterized by FT-IR, 1H NMR, DSC, and TGA. The gel, melt flow rate, hot-set elongation, and tensile properties were also measured. The formation of networks was confirmed by the presence of gel and the shape recovery after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
3
14
0
1
Order By: Relevance
“…In fact, the yields of copolymers are 2–3 times that of PPC ( Table 1 ). In combination with previous studies on the CO 2 /PO/third monomer copolymerization catalyzed by ZnGA, 27 , 28 , 52 , 53 it is shown that the polymer yield increased when the third monomer was cyclic anhydrides but decreased when it was epoxides, when compared with the CO 2 /PO copolymerization. This related to the higher activity of cyclic anhydrides/PO copolymerization than epoxides/CO 2 .…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…In fact, the yields of copolymers are 2–3 times that of PPC ( Table 1 ). In combination with previous studies on the CO 2 /PO/third monomer copolymerization catalyzed by ZnGA, 27 , 28 , 52 , 53 it is shown that the polymer yield increased when the third monomer was cyclic anhydrides but decreased when it was epoxides, when compared with the CO 2 /PO copolymerization. This related to the higher activity of cyclic anhydrides/PO copolymerization than epoxides/CO 2 .…”
Section: Resultssupporting
confidence: 78%
“…The multifunctional monomer always contains several epoxides, isocyanates, or cyclic carboxylic anhydrides, such as vinylcyclohexene dioxide, 35 diphenylmethane diisocyanate, 36 1,2,7,8-diepoxyoctane, 37 1,2,9,10-diepoxydecane, 37 pyromellitic dianhydride, 27 triglycidyl isocyanurate, 38 and bicyclo(2,2,2)oct-7-ene-2,3,5,6-tetracarboxylic dianhydride. 28 Itaconic anhydride that contains both C=C bond and cyclic anhydride was also used as a third monomer to prepare cross-linked PPC. 39 In addition, our group prepared PPC with networks by CO 2 /PO/MA/furfuryl glycidyl ether copolymerization, 40 in which the functional groups that can react with each other were introduced into the PPC pendants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic silylated PPC following hydrolysis reaction can also form cross-linked PPC [32,33]. Compared with the two-step method, PPC can be obtained directly by one-step terpolymerization of PO and CO 2 with diepoxides [15,34], dianhydrides [35,36], or mixed monomers [37]. Sometimes, the addition of diepoxides in the CO 2 /PO copolymerization does not form cross-linked PPC [38,39], which may be related to the reactivity of the diepoxides.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its low decomposition temperature, it is commonly used as a binder for tape casting processes and abrasive substrates production . While its low temperature and clean decomposition is advantageous from a burn off stand point, it limits its practical usage as a bulk product, along with the fact that it is an amorphous polymer with T g close to room temperature . For this reason, there have been many efforts to modify PPC through compounding with other bio‐ and petroleum‐based resins such as poly(lactic acid) (PLA), poly(butylene succinate) (PBS), polycaprolactone, polyoxymethylene, ethylene‐vinyl‐alcohol, and poly(vinyl alcohol), and fillers likes wood flour, natural fibers, and calcium carbonate .…”
Section: Introductionmentioning
confidence: 99%